Photosynthesis under Biotic and Abiotic Environmental Stress - Allakhverdiev, Suleyman; Ivanov, Alexander G.; Brestic, Marian (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Dive into the fascinating world of photosynthesis through the latest publications. This comprehensive work delves deep into the intricate regulatory mechanisms that underpin the vital process of photosynthesis. From the molecular reactions at the core to the overarching responses of entire plants, explore the diverse facets of this fundamental phenomenon. Discover how plants adeptly adapt to an ever-changing and often challenging environment. Gain valuable insights with real-world applications, spanning agriculture, forestry, and biotechnology. Whether you're a scientist, educator, or enthusiast, this reprint promises to unravel the mysteries of life's essential processes. Join us in this exploration of photosynthesis as we bridge the gap between scientific inquiry and practical knowledge, ensuring a sustainable future for both natural ecosystems and cultivated environments.